THE IMPACT OF INSTAGRAM IN-APP ADVERTISING TO CONSUMER AWARENESS OF THE NEW MOBILE GAMES (CASE STUDY: ADOLESCENTS IN TOMOHON) - Pangkerego, Ivan C.; Tumbuan, Willem J. F. A.; Rumokoy, Farlane S. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: This research designed to analyze the impact of Instagram in-app advertising to consumer awareness of the new mobile games using the Simple Linear Regression analysis. The variables are Instagram in-app advertising as independent variable and consumer awareness as the dependent variable. The object of this research is the adolescents in Tomohon. The respondents are the young people 17 years old until 19 years old, those people are still in adolescents category. The finding is Y = 0.209 + 0.819 (X). The coefficient of determination is defined by R2 =0.544, or R square is 54.4% which means Consumer Awareness is able to be explained by Instagram in-app advertising and the rest 45.6% are caused by the other factors. Based on the hypothesis testing by F-Test and T-test, the result has proven that there is linear relationship between the variables partially and simultaneously. The F-Test and the T-test also shows that the Instagram in-app Advertising significantly influences the Consumer Awareness. Keywords: Instagram, in-app advertising, Consumer Awareness, Adolescent